Heparin, Low Molecular Weight Heparin, and Non-Anticoagulant Derivatives for the Treatment of Inflammatory Lung Disease - Janis Kay Shute (MDPI AG, 2023)
Unfractionated heparin has multiple pharmacological activities beyond anticoagulation. These anti-inflammatory, anti-microbial, and mucoactive activities are shared in part by low molecular weight and non-anticoagulant heparin derivatives. Anti-inflammatory activities include inhibition of chemokine activity and cytokine synthesis, inhibitory effects on the mechanisms of adhesion and diapedesis involved in neutrophil recruitment, inhibition of heparanase activity, inhibition of the proteases of the coagulation and complement cascades, inhibition of neutrophil elastase activity, neutralisation of toxic basic histones, and inhibition of HMGB1 activity. This review considers the potential for heparin and its derivatives to treat inflammatory lung disease, including COVID-19, ALI, ARDS, cystic fibrosis, asthma, and COPD via the inhaled route.